2020
DOI: 10.3126/pravaha.v25i1.31934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cash Management on Profitability in Small Manufacturing Organization

Abstract: Small businesses are vital for economic development and employment generation. The implementation of sound cash management practices is essential to ensure the profitability. The aim of the study was to identify the impact of cash management on profitability. This study was adopted correlation research design. Purposive sampling method was adopted while undertaking research. 80 samples were considered while collecting data. The sample structure consisted of small and medium manufacturing businesses in the Kirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The result shows that for one unit increase in the business management, it resulted in an increase by a factor of 2.201 (e 0.789 , p < 0.05) in the odd of being in the higher income group. This finding is in agreement with Pandey (2019) which showed that business management practices among microentrepreneurs have significantly contributed to the business's income. Table 13 shows parallel line test to evaluate the proportional odds assumption, which stated that the slope coefficients in the model is the same across response categories.…”
Section: Ordinal Logistic Regressionsupporting
confidence: 92%
“…The result shows that for one unit increase in the business management, it resulted in an increase by a factor of 2.201 (e 0.789 , p < 0.05) in the odd of being in the higher income group. This finding is in agreement with Pandey (2019) which showed that business management practices among microentrepreneurs have significantly contributed to the business's income. Table 13 shows parallel line test to evaluate the proportional odds assumption, which stated that the slope coefficients in the model is the same across response categories.…”
Section: Ordinal Logistic Regressionsupporting
confidence: 92%
“…Moreover, they often perform bank reconciliation. Pandey (2018) discussed that cash flow should be adequate, otherwise the business will become technically insolvent. Cash management deals with handling cash inflows and cash outflows of the day-to-day business operations which is vital in every transaction in the food industry sector.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Conversely, an analytic study was conducted in Nepal regarding the relationship between cash management and profitability in small and medium manufacturing businesses (Pandey 2018). Using correlation and regression analysis, the study showed a low degree of positive correlation between the above variables, that is, as cash management increased, profitability increased also albeit insignificantly.…”
Section: Introductionmentioning
confidence: 98%
“…With this, profitability has a significant effect on the growth of SMEs (Raharja & Kostini, 2019) and lack of enterprise profit appears to be a binding constraint to their growth (Shitaye & Elgammal, 2022). Most Micro, Small and Medium Enterprises (MSMEs) are not profitable and poor utilization of assets, poor cash management practices and difficulty to produce equity returns are the major problems (Mayanja, 2020; Pandey, 2020). MSEs profitability is decreasing as they failed to apply financial statement analysis, made unplanned withdrawals of money for personal use, manage their working capital poorly and faced shortage of finance (Abera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%